Diagrams of Deformation of Cement Composites Reinforced with Steel Wire Fiber - Yuri V. Pukharenko; Dmitry A. Panteleev; Mikhail I. Zhavoronkov (Academia: Архитектура и строительство, 2018)
Modern construction practice acquires such a tendency, at which it is required to use materials with increased physical, mechanical and operational characteristics, and at the same time, do not require significant material, labor and energy costs for their production. One of the most promising building materials that meet the requirements is fiber-reinforced concrete. However, the increase in the volume of its use is limited by the insufficient degree of study of its properties and characteristics. This problem is aggravated by the constantly expanding range of reinforcing fibers, which can give composites produced on their basis, completely different properties and characteristics.